La costruzione sociale e la teoria dei problemi sociali: un contributo all’eredità di John Kitsuse - Weinberg, Darin (SocietàMutamentoPolitica, 2018)
In this article, I trace a brief genealogy of the debate John Kitsuse inaugurated over objectivism in constructionist social problems theorizing and propose a solution to the dilemmas to which this debate has given rise. The proposed solution draws from postfoundationalist philosophers, sociologists, and historians of science who have radically reformulated the nature of empirical research such that the antinomy between subjectivism and objectivism is largely dissolved and the conceptual chasm between interpretive understanding and causal explanation is all but eliminated. Building on this literature, I describe and defend a middle road between Kitsusian constructionists’ principled denials of any causal relationship between claims-making activities and the conditions those activities presumably concern and the theoretically moribund brands of objectivism that Kitsuse and his constructionist colleagues have been properly concerned to overcome.